Management of anastomotic leakage after colorectal resection: survey among the German CHIR-Net centers - Şandra-Petrescu, Flavius Ionuţ; Rahbari, Nuh Nabi; Birgin, Emrullah; Kouladouros, Konstantinos; Kienle, Peter; Reißfelder, Christoph; Tzatzarakis, Emmanouil; Herrle, Florian (Journal of Clinical Medicine, 2023)
(1) Background: A widely accepted algorithm for the management of colorectal anastomotic leakage (CAL) is difficult to establish. The present study aimed to evaluate the current clinical practice on the management of CAL among the German CHIR-Net centers. (2) Methods: An online survey of 38 questions was prepared using the International Study Group of Rectal Cancer (ISREC) grading score of CAL combined with both patient- and surgery-related factors. All CHIR-Net centers received a link to the online questionary in February 2020. (3) Results: Most of the answering centers (55%) were academic hospitals (41%). Only half of them use the ISREC definition and grading for the management of CAL. A preference towards grade B management (no surgical intervention) of CAL was observed in both young and fit as well as elderly and/or frail patients with deviating ostomy and non-ischemic anastomosis. Elderly and/or frail patients without fecal diversion are generally treated as grade C leakage (surgical intervention). A grade C management of CAL is preferred in case of ischemic bowel, irrespective of the presence of an ostomy. Within grade C management, the intestinal continuity is preserved in a subgroup of patients with non-ischemic bowel, with or without ostomy, or young and fit patients with ischemic bowel under ostomy protection. (4) Conclusions: There is no generally accepted therapy algorithm for CAL management within CHIR-Net Centers in Germany. Further effort should be made to increase the application of the ISREC definition and grading of CAL in clinical practice.
Veröffentlicht: 27. Juli 2023
Gesehen am 26.09.2023